Drying kinetics and characteristics of Acori tatarinowii rhizoma under hot air thin-layer drying at different temperatures - Yingna Le; Kun Shi; Chengfu Wang; Jingying Guo; Yaohui Ye; Yuexing Ma; Ruiping Wang; Fangyan Cai; Shaolong Ma; Jinlian Zhang; Lingyun Zhong (Scientific Reports)
Abstract The primary objectives of this study were to evaluate the kinetics of Acori tatarinowii rhizoma (ATR) and to investigate how hot air drying at different temperatures affected the surface texture and sensory quality of the ATR. The drying kinetics of ATR were evaluated at five temperature levels (35, 45, 55, 65, and 75 ℃). Among the tested models, the Cubic model showed the best performance. It exhibited higher fitting accuracy with ( $${R}^{2}=0.978-0.999$$ ) across all temperature conditions. Moreover, this model demonstrated lower error metrics ( $${χ }^{2}$$ , SSE, and RMSE) with minimal variations between temperatures. These results indicate that the Cubic model is the most suitable for characterizing the drying behavior of ATR under the studied conditions. The activation energy ( $${E}_{a}$$ ) value of ATR dried by hot air drying was calculated as $$33.145\text{kJ}· {mol}^{-1}$$ . Complementary analyses using scanning electron microscopy(SEM) and Heracles NEO ultra-fast gas chromatography analysis revealed temperature-dependent microstructural changes and volatile profile variations in ATR. 11 odor components were identified, with key thermal-modulated volatility patterns observed. Notably, methyl dodecanoate showed significantly higher concentrations at 65 °C than at 75 °C (P < 0.05). Overall, combined with the apparent properties of scanning electron microscopy and the color results of the colorimeter, thin-layer hot air drying at 65 ℃ can significantly enhance the final quality of ATR while preserving the odor profile and color properties and providing optimum medicinal characteristics. This study provides the first comprehensive analysis of drying temperature effects on ATR, uniquely correlating thermal parameters with surface morphology, microstructural evolution, and volatile compound preservation. By resolving the longstanding knowledge gap in ATR post-harvest processing, the work establishes quantitative criteria for industrial drying optimization, offering a science-based framework to balance efficiency and phytochemical quality.